Hemicellulose/poly(acrylic acid) semi-IPN magnetic nanocomposite hydrogel for lysozyme adsorption - Tao Zhang; Xiao-Feng Sun (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2020)
A novel hemicellulose-based magnetic nanocomposite hydrogel was synthesized with modified Fe3O4 nanoparticles using H2O2-Vc as a green initiator system. The nanocomposite hydrogels were characterized by FT-IR, SEM and VSM, and the swelling properties of the hydrogels were also studied. The result demonstrated that the nanocomposite hydrogels had excellent pH sensitivity and magnetic property. This study found that the increases of the contents of Fe3O4 nanoparticles resulted in higher cross-linking density, and the swelling ratio of the prepared hydrogels decreased. The VSM analysis showed that the magnetic hydrogels had superparamagnetic property, and the magnetization intensity increased with an increase in the content of Fe3O4 nanoparticles. The adsorption isotherm study of lysozyme demonstrated that both of Freundlich and Temkin isotherms models can describe the adsorption of lysozyme on the magnetic hydrogels. The smart swelling property and the high adsorption capacity of the magnetic hydrogel would expand it applications in drug delivery and magnetic separation aspects.